Anti-bacterial property and anti-nutritional contents of five wild fruits of Assam, India - Anuck Islary, Jatin Sarmah, Sanjay Basumatary (Journal of Applied Pharmaceutical Science, 2018)
Background: Wild fruits have traditionally been important food sources for rural population which are known to contain many biologically active compounds that can help in the prevention of several diseases. Objective: To investigate the anti-bacterial property and anti-nutritional contents of Grewia sapida Roxb. ex DC., Ottelia alismoides (L.) Pers., Aporosa dioica (Roxb.) Muell.-Arg., Antidesma bunius (L.) Spreng., and Eugenia operculata Roxb. fruits obtained in Assam, India. Methods: The methanolic extracts of five wild fruits were studied for anti-bacterial activities against two strains of gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) and two strains of gram-negative bacteria (Escherichia coli and Proteus vulgaris) using the disc diffusion method. The anti-nutritional contents such as oxalate, phytate, tannins, saponins, and alkaloid were also assessed following the reported procedures. Results and Conclusion: All the fruit extracts exhibited different degrees of anti-bacterial activities. E. operculata, A. dioica, and O. alismoides extracts were the most effective extracts, which showed strong anti-bacterial activities against the studied bacteria. The five wild fruits showed varied concentrations of anti-nutritional factors and very high levels of anti-nutritional compounds were not observed.
Keywords: Anti-bacterial activity, anti-nutritional content, MBC, MIC, wild edible fruits.